Analisis Persepsi Manajemen Risiko Keuangan dalam Koperasi Simpan Pinjam: Studi pada Faomasi Baluse Mandiri di Ungaran - Zebua, Elman Septianus; Hendrajaya, Hendrajaya (Mahesa Research Center, 2025)
This article aims to explore stakeholder perceptions of financial risk management in Koperasi Simpan Pinjam Faomasi Baluse Mandiri, Ungaran. The focus of the study is on the implementation of financial risk management policies and the challenges faced in managing cooperative risks. To approach this issue, theoretical references on financial risk management and cooperative governance were utilized. Data were collected through in-depth interviews with cooperative management, financial staff, and cooperative members, as well as direct observations and document analysis. The data were analyzed qualitatively using a thematic approach. The findings indicate that the cooperative has implemented policies such as loan restrictions, creditworthiness evaluation, income diversification, and regular financial monitoring and audits. These policies have contributed to reducing the risk of bad loans and enhancing the cooperative's sustainability. However, the cooperative still faces challenges such as low member awareness of financial policies, economic uncertainty affecting the cooperative's financial stability, varying levels of member compliance in loan repayments, and limited resources for risk management. This study concludes that to strengthen financial risk management, the cooperative needs to improve members' financial literacy, adopt digital technology in financial systems, and implement risk mitigation strategies that are more adaptive to economic and regulatory changes.